Observation Methods in Evaluating Early Childhood Learning in Kindergarten - Muhamad Ali Gunawan; Syukri Hamzah; Hadiwinarto Hadiwinarto; Sudarwan Danim (STAI Hubbulwathan Duri, 2023)
This study aimed to explore observation methods for evaluating early childhood learning in Kindergarten Group B at Aisyah Kindergarten Lubuklinggau. The research involved 32 students, aged five years, comprising 12 boys and 20 girls. A qualitative approach was employed, utilizing observation, interviews, and documentation. The study identified various observation methods, including anecdotal notes, running records, checklists, time sampling, and event sampling, each with distinct advantages and limitations. Anecdotal records provided detailed insights into individual student behaviors, while running records offered comprehensive observations over time. Checklists allowed for rapid assessments but lacked depth, focusing primarily on the presence or absence of specific behaviors. Time sampling concentrated on the frequency of behaviors, and event sampling added context by recording the causes and effects of behaviors, though it risked missing key behaviors due to its predetermined scope. These methods collectively serve to assess children's development and learning progress. The evaluation of early childhood education (PAUD) is critical for understanding the effectiveness of educational programs in shaping children's behavior and attitudes, as well as for guiding continuous improvement. However, challenges remain in aligning evaluation strategies with curriculum goals and selecting the most appropriate assessment tools. Despite these challenges, systematic evaluation and ongoing refinement efforts by PAUD educators are essential to optimize children's developmental outcomes and prepare them for future educational challenges.